Effect of Methionine Deficiency on the Growth Performance, Serum Amino Acids Concentrations, Gut Microbiota and Subsequent Laying Performance of Layer Chicks - Liu, Yafei; Wang, Dehua; Zhao, Lihong; Zhang, Jianyun; Huang, Shimeng; Ma, Qiugang (Frontiers in Veterinary Science, 2022)
This study was conducted to investigate the effect of methionine (Met) deficiency in the rearing period on the growth performance, amino acids metabolism, intestinal development and gut microbiome of egg-laying chicks and the continuous effects on the performance, egg quality, and serum amino acids metabolism of the subsequent development process. Three hundred sixty one-day-old chicks were randomly divided into two groups and fed on a basal diet (NC group, Met 0.46%) and Met deficiency diet (Met- group, Met 0.27%). Each group included six replicates with 30 chicks per replicate. The trial lasted 6 weeks (0–6 weeks), both groups were fed the same basal diet which met the needs of Met during the observation period (7–24 weeks). Results showed that Met deficiency significantly decreased (P < 0.05) body weight (BW), average daily weight gain (ADG), average daily feed intake (ADFI) and tibia length (TL) compared to the NC group during the trial period (0–6 weeks). Also, Met deficiency dramatically increased (P < 0.05) feed conversion ratio (FCR) during the trial and observation period (7–24 weeks). In addition, during the observation period, the BW and ADG were decreased (P < 0.05) in the Met- group. Moreover, Met- group decreased (P < 0.05) villi height and villi height/crypt depth ratio in jejunum at 6th weeks. In addition, the concentrations of serum main free amino acids (FAA) in the Met- group were significantly increased (P < 0.05) at 6th weeks, while were decreased at 16th weeks. Based on the α-diversity and PCoA analysis in β-diversity, there were no significant differences in the cecal microbial composition between NC and Met- groups. However, the LEfSe analysis revealed that differential genera were enriched in the NC or Met- groups. The Haugh unit, shell thickness and egg production in the Met- group were significantly lower (P < 0.05) than in the NC group. In conclusion, these results revealed that dietary supplementation of appropriate Met could substantially improve the growth performance, host amino acid metabolism and intestinal development and continuously improve the laying performance and thus boost the health of growing hens.